(untitled) (Research, Society and Development, 2024)
Life Cycle Thinking (LCT) is considered a qualitative study because it describes the environmental impacts of a product or process. This perception allows us to identify the potential effects and resources used, allowing us to structure sustainable ideas, identifying and developing innovative solutions. Establishing the life cycle of a product requires planning and understanding the stages of the production chain, the continuous assessment of processes and their environmental functions, from the extraction of raw materials, transportation, manufacturing process, delivery to the customer and final disposal. Although LCT is considered a philosophy, Life Cycle Assessment (LCA) is a quantitative scientific method that allows you to express this thought. Through life cycle concepts and tools, it becomes possible to define the stages of a product’s life cycle, assist decision makers in data analysis and implement sustainability with appropriate strategies and actions. However, the objective of this review is to describe concepts and definitions about LCT and LCA. It is hoped that researchers will be able to guarantee true sustainability in production, which will require careful assessment and multiple considerations based on an in-depth reflection on the product’s life cycle.